Evaluation Of Traffic Weaving Behavior And Performance At Malaysian Urban Highway Weaving Segments - Abdullah, Rohaya (2020)
A weaving section is defined when there is a merging and a diverging road formed together. The conflict at the traffic changing lane, where crossing to the desired exit or entry point happens will consequently reduce the speed of the section and creating bottlenecks at the highway facilities. The flow on an urban highway will be interrupted if an obstruction happens along the downstream highway because of the high traffic volume. As a result, the highway will be unable to maintain the desired level of service for that particular section of the highway. This phenomenon is a daily event on Malaysian urban highways. The objective of this study includes understanding the weaving behaviour, evaluating the performance of the weaving section, evaluating the mitigation measure implemented and recommending a further study to amend the current guideline on the weaving of the Malaysia urban highway. The data were collected at four locations at urban highways which is daily having problem of bottleneck caused by the weaving activities. In this research, a weaving analysis method which included the small lorry and motorcycles, is used to evaluate the LOS of the weaving segment to suit the Malaysian traffic condition. The result is then compared with the HCM 2010 weaving analysis method. It is found that the result of LOS by this modified analysis method is higher than the HCM 2010. From the data, it is found that the motorcycle is the second highest traffic and it is also taken into account in the modified weaving analysis method. An implementation of mitigation at the weaving segment by adding an additional lane was then analysed to evaluate the effectiveness. It is found that adding an additional lane at the weaving segment will increase the capacity of the segment and reduce the lane changing rate. Finally, recommendation for an amendment of the Guideline of Toll Road System – Design Standard were proposed to update according to real data at site.